Analysis of Input and Output Ripples of PWM AC Choppers - Dahono, Pekik Argo; Amirudin, Dessy; Rizqiawan, Arwindra; Deni, Deni (ITB Journal Publisher, LPPM ITB, 2008)
This paper presents an analysis of input and output ripples of PWM AC choppers. Expressions of input and output current and voltage ripples of single-phase PWM AC choppers are first derived. The derived expressions are then extended to three-phase PWM AC choppers. As input current and output voltage ripples specification alone cannot be used to determine the unique values of inductance and capacitance of the LC filters, an additional criterion based on the minimum reactive power is proposed. Experimental results are included in this paper to show the validity of the proposed analysis method.